Determination of Palatal Soft Tissue Thickness and Safe Zone for Palatal Soft Tissue Harvest Using CBCT: A Retrospective Study - Hanan Aldhanhani; Bhavna Jha Kukreja; Sesha Reddy; Jovita D’souza; Hossam Abdelmagyd (International Journal of Dentistry)
Aim. Our decision to conduct this study was motivated by the dearth of knowledge on geographical variations in the thickness of the palatal masticatory mucosa. The aim of the present study is to comprehensively analyze the palatal mucosal thickness and indicate the safety zone for palatal soft tissue harvesting using cone beam computed tomography (CBCT). Material and Methods. As this was a retrospective analysis of cases previously reported to the hospital, written consent was not acquired. The analysis was carried out on 30 CBCT images. Two examiners evaluated the images separately to avoid bias. Measurements were done from the midportion of the cementoenamel junction (CEJ) to the midpalatal suture in a horizontal line. Measurements were recorded from the maxillary canine, first premolar, second premolar, first molar, and second molar and were marked in axial and coronal sections at distances of 3, 6, and 9 mm from the CEJ. The relationship between palate soft tissue thickness in relation to each tooth, palatal vault angle, teeth, and the greater palatine grove was evaluated. Differences in the palatal mucosal thickness according to age, gender, and tooth site were evaluated. Categorical data were presented as frequencies and percentages. Numerical data are presented as mean and standard deviation values. They are explored for normality using Shapiro–Wilk’s test. Data are normally distributed and are analyzed using one-way ANOVA followed by Tukey’s post hoc test for independent variables and paired t-test for repeated measures. The significance level is set at p≤0.05 for all tests. Statistical analysis is performed with R statistical analysis software version 4.1.3 for Windows. Results. For sex and nationality, there was no significant association (p>0.05), while for age, cases 35 years and older had significantly higher mucosal thickness than cases younger than 35 years old (p<0.001). For all teeth, the association was statistically significant (p<0.001). For the canine and first premolar, cases with deep angles had significantly higher mean values than those with moderate angles (p<0.001). For other teeth, cases with deep angles had significantly higher mean values than other angles (p<0.001). Conclusion. Palatal mucosal thickness varied significantly from the canine to the second molar; the most appropriate site for graft harvesting is the canine to second premolar area which is 9–12 mm from the midpalatal suture aspect and is considered a safe zone for harvesting palatal graft.